Predicting the Development of Adult Nature Connection Through Nature Activities: Developing the Evaluating Nature Activities for Connection Tool - Carr, Victoria; Hughes, Joelene (Frontiers in Psychology, 2021)
Nature Connection is considered an important driver of conservation behavior. Consequently, conservation organizations run many activities aiming to increase nature connection among participants. However, little is known about which activities are most effective at doing this and why. This study developed the Evaluating Nature Activities for Connection Tool (ENACT), to evaluate the effectiveness of activities for increasing participants’ nature connection and nature-related intentions. ENACT comprises 11 activity aspects identified through two research phases. In Phase 1, a literature search, focus group and interviews identified desired, short-term behavioral outcomes of nature activities and variables that might promote these. In Phase 2, 241 adults completed a pilot survey immediately post-nature activity, with one-month follow-up (N=145), to evaluate the impact of participation on nature connection, nature-related behavioral intentions and behaviors. ENACT correlated with nature connection measures and offered incremental validity in predicting nature-related behavioral intentions and self-reported behaviors after one month.